Microbiological Profile, Histopathological Severity, Drug Utilization, and Nutritional Risk Factors in Patients with Diabetic Foot Ulcers - Rizwan Saeed, Ammara Shafqat, Hannah Saleemi, Rubina Kashif, Tehreem Saif, Hamid Nawaz Khokhar, Hafsah Maryam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Diabetic foot ulcers (DFUs) are a major complication of diabetes mellitus, associated with high morbidity, infection risk, and amputation. Multiple factors including microbial infection, histopathological damage, irrational drug use, and poor nutritional status influence disease severity and healing outcomes. Methods: This cross-sectional study was conducted on 120 patients with diabetic foot ulcers from January 2022 to January 2023 at Khawaja Muhammad Safdar Medical College, Sialkot, Pakistan, and Sahara Medical College, Narowal, Pakistan. Microbiological analysis was performed using wound cultures, while histopathological grading was done through tissue biopsy. Drug utilization patterns were assessed from clinical records. Nutritional status was evaluated using body mass index, serum albumin, and hemoglobin levels. Statistical analysis was performed using SPSS version 26, with p < 0.05 considered significant. Results: Gram-negative organisms predominated, with Pseudomonas aeruginosa (30.0%) and Escherichia coli (20.8%) being the most common isolates. Severe histopathological grades (Grade III–IV) were observed in 50.0% of patients. Polypharmacy was noted in 65.8% of cases, and empirical antibiotic therapy was used in 73.3% of patients. Nutritional deficiencies were highly prevalent, with hypoalbuminemia (58.3%), anemia (46.7%), and low BMI (25.8%). A significant association was found between poor nutritional status and increased ulcer severity (p < 0.001). Conclusion: Diabetic foot ulcers are characterized by polymicrobial infections, advanced tissue damage, irrational antibiotic use, and significant nutritional deficiencies. A multidisciplinary approach incorporating culture-guided therapy, rational drug use, and nutritional optimization is essential to improve clinical outcomes and reduce complications. Keywords: Diabetic foot ulcer, microbiological profile, histopathology, antibiotic utilization, malnutrition, wound healing